Smokers who have not tried alternative nicotine products: a 2019 survey of adults in Great Britain - Erikas Simonavicius; Ann McNeill; Hazel Cheeseman; Deborah Arnott; Leonie S. Brose (BMC, 2020)
Abstract Aims Switching from smoking to using nicotine replacement therapy (NRT), electronic cigarettes (e-cigarettes) or heated tobacco products can reduce tobacco-related health risks. However, not all smokers in Great Britain have tried these products. This study aimed to identify and describe smokers who have never tried alternative nicotine products. Methods We analysed cross-sectional survey data of smokers (n = 1777) from a representative adult sample from Great Britain. The online survey was run in March 2019. The proportion of smokers who had never used alternative nicotine products was measured. A multivariate logistic regression assessed the association between never having used alternative nicotine products and sociodemographic and smoking characteristics and motivation to stop smoking. Results One in four smokers (27.8%, 95% CI 25.8-29.9%) had never tried NRT, e-cigarettes or heated tobacco products. These smokers were more commonly from Black and Minority than White ethnic groups (AOR = 1.55; 95% CI 1.02-2.31), were more likely to smoke up to 10 versus more cigarettes per day (AOR = 1.52; 95% CI 1.14-2.03) and to report low versus moderate or high motivation to stop smoking (AOR = 1.79; 95% CI 1.20-2.74). Conclusion Light smokers, those unmotivated to stop and smokers from Black and Minority ethnic groups are less likely to have ever tried alternative nicotine products. Different approaches are needed to facilitate harm reduction and smoking cessation among these groups of smokers.